Usage of anglicisms in the context of current language situation in Ukraine - Yuliia O. Molotkina (Психолінгвістика)
The article deals with the analysis of usage of borrowed English lexemes in the contex of the current language situation in Ukraine. It is proved that due to the several historical, political and cultural factors other languages influenced Ukrainian throughout all periods of its existence. The most considerable impact on Ukrainian had Polish and Russian languages as the great part of Ukrainian territory had been under Polish and Russian control for a long time. Both these countries tried to perform language and cultural assimilation. Russian and Polish languages still have a strong influence on Ukrainian one. These days Ukraine faces quite difficult language situation. Due to the unofficial bilingualism and long-term co-existence of Ukrainian and Russian languages, Ukrainian has serious purity issues. A huge number of anglicisms in modern Ukrainian discourse makes language situation more complicated. English language prestige and popularity of foreign words lead the excessive and often inappropriate usage of borrowed English words. Excessive using of anglicisms distorts grammar norm of Ukrainian language and ruin its purity.